Análisis sobre pintadas e inscripciones en el sitio Mansión Seré (Morón, Provincia de Buenos Aires) (Comechingonia. Revista de Arqueología, 2011)
This paper is presenting the results of analysis carried out on paintings and writings produced on the walls of Mansion Sere (Morón, Buenos Aires). This study will take into account two main sources: on one hand the preserved material support (only in two specific cases), on the other hand there are 133 photographs which were taken between 1930 and 1985. The precise recovery of each mark might lead us to discover the techniques used, the date it was made and its meaning. The study of these graphic elements will enable us to comprehend their use, their motives and the communicative function of each mark. It was possible to see an intense marking of the walls of Mansión Seré after this place had functioned as a Clandestine Center of Detention (C.C.D.) between 1978-1985. The presence of writings on the walls made by ex disappeared prisoners while they were arrested in that place, is mentioned in different testimonies. Beyond this circumstance and its special meaning, this fact is a way of memorizing the appropriation of a space.